PENGARUH KEPUASAN KERJA DAN KOMITMEN ORGANISASIONAL PADA KINERJA KARYAWAN DI NATYA HOTEL, KUTA BALI - Sri Wahyudi, Ni Komang; Sudibya, I Gede Adnyana (E-Jurnal Manajemen, 2016)
This study aims to determine the effect of  job satisfaction on organizational commitment, job satisfaction to determine the effect on employee performance, to determine the effect of organizational commitment to employee performance in Natya Hotel, Kuta, Bali. This research was conducted in Natya Hotel Kuta Bali. Sampling method nonprobability sampling that the saturation sampling with 45 respondents. Data analysis method used is the analysis of the path (path). The analysis showed that job satisfaction is positive and significant effect on organizational commitment, job satisfaction and significant positive effect on employee performance and organizational commitment and significant positive effect on employee performance. Based on the research results, the company Natya Hotel Kuta Bali should retain and increase the job satisfaction of employees to be more motivated to work thus increasing commitment to the company and improve performance.
Keywords: Job Satisfaction, Organizational Commitment and Employee Performance